Age‐specific variation in relationship between moult and pre‐migratory fuelling in Wood Sandpipers Tringa glareola in southern Africa. (January 2017) - Remisiewicz, Magdalena; Tree, Anthony J.; Underhill, Les G.; Burman, Marc S.
Abstract : Trans‐equatorial avian migrants tend to breed, moult and migrate – the main energy‐requiring events in their lifecycle – at different times. Little is known about the relationship between wing moult and pre‐migratory fuelling in waders on their non‐breeding grounds, where time is less constrained than during their brief high‐latitude breeding season. We determined age‐related strategies of Wood Sandpipers Tringa glareola to balance the energetic demands of primary moult against pre‐migratory fuelling in southern Africa by analysing body mass and primary moult at first capture of 1721 birds mist‐netted in 1972–96 at waterbodies in Zimbabwe. Adults moulted all their primaries in August–December, but immatures underwent a supplemental moult of varying numbers of outer primaries in December–April, close to departure. We used locally weighted linear regression to estimate trends in Wood Sandpiper body mass from 1 July to 1 May. They maintained low mass from arrival in July–September to February–early March. Adults fuelled from 10 February to 1 May at a mean rate of 0.25 g/day (sd = 0.16). Most adults (98%) began fuelling 10–75 days after completing primary moult. Immatures fuelled from 4 March to 13 April at 0.24 g/day (sd = 0.14). They used varying strategies depending on their condition: a brief gap between moult and fuelling; an overlap of these processes near departure, leading to slower fuelling; or skipping fuelling altogether and staying in southern Africa for a 'gap year'. Immatures moulting three or five outer primaries fuelled more slowly than post‐moult birds. Immatures moulting four outer primaries started fuelling 3 weeks later but at a higher rate than did post‐moult birds of this group. In post‐moult immatures, the later they ended moult, the later and faster they fuelled. The heaviest adults and immatures using all moult patterns accumulated fuel loads of c . 50% of lean body mass, and could potentially cross 2397–4490 km to reach the Great Rift Valley in one non‐stop flight. Immatures were more flexible in the timing and extent of moult and in the timing and rate of fuelling than adults. This flexibility enables inexperienced Wood Sandpipers to cope with inter‐annual differences in feeding conditions at Africa's ephemeral inland waterbodies.